2017
DOI: 10.1007/s11908-017-0561-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Manifestation of Chikungunya Virus

Abstract: In the last 5 years, CHIKV endemicity has spread to the Americas and the number of cases of CHIKV-related disease has dramatically increased. Evidence suggests increasing neurovirulence of the virus, particularly among the critically ill. The spectrum of neurologic manifestations of the disease includes encephalitis, myelitis, and Guillain-Barre syndrome, but isolated reports of cranial neuropathies and cognitive deficits associated with recent infection also are reported. Though neurologic symptoms associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…Despite the lack of association between CHIKV and GBS in the present study, evidence from other studies with different study designs than the ones considered in this review show evidence of causality. A study done during a CHIKV outbreak in Reunion Island in 2006 found an association between CHIKV and occurrence of GBS in the absence of any other plausible factor associated with the syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of association between CHIKV and GBS in the present study, evidence from other studies with different study designs than the ones considered in this review show evidence of causality. A study done during a CHIKV outbreak in Reunion Island in 2006 found an association between CHIKV and occurrence of GBS in the absence of any other plausible factor associated with the syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Computational prediction of CHIKV recoding signals CHIKV sequences were imported from NCBI into the Dinman laboratory frameshifting database (http://prfdb.umd. edu) 6 (59). The conserved opal stop codon at the 3Ј end of the nsP3 gene and the U UUU UUA slippery site in the 6K gene were used to identify the sequences harboring the CHIKV TCR and Ϫ1 PRF stimulatory elements, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293T or U-87 MG cells were seeded at 0.6 ϫ 10 5 cells in 0.5 ml/well for 24-well plates for Dual-Luciferase transfections; and 1 ϫ 10 6 cell in 2 ml/well for 6-well plates for BiFl transfections in appropriate complete growth media (Dulbecco's modified Eagle's medium or Eagle's minimum essential medium). Following a 24-h incubation period, control and experimental reporter plasmids were then transfected into cells using Lipo- 6 Please note that the JBC is not responsible for the long-term archiving and maintenance of this site or any other third party-hosted site.…”
Section: Plasmid Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection of CHIKV causes debilitating rheumatic diseases and inflammatory disorders which are generally non-fatal. However, in rare cases CHIKV infection can cause neurodegenerative disorders such as meningoencephalitis, myelitis, and Guillain-Barre syndrome (Gerardin et al, 2016; Brizzi, 2017). …”
Section: The Relationship Between Viral Infections and Neuroinflammatmentioning
confidence: 99%